Variation in soil bacterial communities by long-term application of organic and inorganic fertilizers in rice - Shanthpure, Ashwini; Girija, Devaki; Sidharthan, Panchami Pottekkat; Peedikakkal, Moosa Puthen; Nair, Sneha Sasidharan (Journal of Cereal Research, 2019)
Fertilization plays important role in increasing the quality of soil and crop productivity. Soil bacterial communities are sensitive indicators of soil quality and their response to long-term fertilization in paddy soils of Kerala remains unexplored. In the present study, we analysed the long term effect of fertilizer regimes viz., organic inputs (ONM), integrated inputs (INM) and inorganic (INF) inputs on bacterial community in paddy soils using NGS sequencing of 16S rRNA genes. The results showed that relative abundance of bacterial communities varied across organic and inorganic fertilizer treatments. The dominant phyla across all the treatments were Actinobacteria followed by Acidobacteria, Proteobacteria and Firmicutes. The long term application of organic and integrated fertilizers clearly increased the abundance of beneficial microbes like Bacillus, Arthrobacter, Bradyrhizobium, Frankia etc in soil. In contrast, continuous use of chemical fertilizers, suppressed the growth of Rhizobium, Azospirillum, Pseudomonas and Burkholderia in rhizosphere soils. Overall, the present study enhanced our understanding of relationship between soil microbiota and functioning of agro ecosystem and support the use of integrated fertilization strategy in rice. DOI:https://doi.org/10.25174/2249-4065/2019/94878